Ecological efficiency in thermoelectric power plants - de Castro Villela, Iraides Aparecida; Silveira, Jose Luz (Elsevier B.V., 2007)
This work evaluates the environmental impact resulting from the natural gas and diesel combustion in thermoelectric power plants that utilize the combined cycle technology (CC), as regarding to Brazilian conditions according to Thermopower Priority Plan JPP). In the regions where there are not natural gas the option has been the utilization of diesel and consequentily there are more emission of pollutants. The ecological efficiency concept, which evaluates by and large the environmental impact, caused by CO2, SO2, NOx and particulate matter (PM) emissions. The combustion gases of the thermoelectric power plants working with natural gas (less pollutant) and diesel (more pollutant) cause problems to the environment, for their components harm the human being life, animals and directly the plants. The resulting pollution from natural gas and diesel combustion is analyzed, considering separately the CO2, SO2, NO2 and particulate matter gas emission and comparing them with the in use international standards regarding the air quality. It can be concluded that it is possible to calculate thermoelectric power plant quantitative and qualitative environment factor, and on the ecological standpoint, for plant with total power of 41441 kW, being 27 170 kW for the gas turbine and 14271 kW for the steam turbine. The natural gas used as fuel is better than the diesel, presenting ecological efficiency of 0.944 versus 0.914 for the latter, considering a thermal efficiency of 54% for the combined cycle. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: ecological efficiency; environmental impact; natural gas; diesel